2015
DOI: 10.1097/brs.0000000000000737
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative/Nitrosative Stress in Patients With Modic Changes

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, when free radical generation exceeds the antioxidant production capacity, oxidative stress occurs in various diseases [ 15 ]. Recently, there has been considerable interest in oxidative stress caused by ROS and its involvement in disease processes [ 16 , 17 ]. The results of the present study showed that 8-iso-PGF 2α (lipid peroxidation product) level was significantly higher in lesional area compared to non-lesional area.…”
Section: Discussionmentioning
confidence: 99%
“…However, when free radical generation exceeds the antioxidant production capacity, oxidative stress occurs in various diseases [ 15 ]. Recently, there has been considerable interest in oxidative stress caused by ROS and its involvement in disease processes [ 16 , 17 ]. The results of the present study showed that 8-iso-PGF 2α (lipid peroxidation product) level was significantly higher in lesional area compared to non-lesional area.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, biological therapy is a potential method for the treatment of IDD, which can avoid the complication of surgery. Numerous researches have shown that oxidative stress participated in the pathological process of IDD [2630, 37]. However, the underpinning molecular mechanism is only partially elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that the level of oxidative stress in the degeneration of cartilaginous endplate was increased, which indicated that oxidative stress was also involved in the degeneration of cartilaginous endplate [30]. Nonetheless, no study was designed to explore the autophagy and apoptosis of cartilaginous endplate under oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the invading bacteria may have a nonskin origination, for example, from the oral cavity, as shown by Rollason et al . in a phylogenetic study [20];The most commonly found bacteria in the disc and herniated discal tissue are different subtypes of P. acnes [20–22];Bacteria with sufficiently virulent characteristics are able to colonize intradiscally [10];This is followed by inflammation and accelerated degeneration that in turn leads to end plate damage and MC changes as seen on MRI scans [10,23,24];Disc-related inflammation will lead to back pain and the injection of anti-inflammatory agents has demonstrated short-term pain reduction in several studies [23,25];A long-term antibiotic regimen results in a 50% reduction of pain in 50% of patients with low back pain following a disc herniation and Modic changes type 1 [12,13]. …”
Section: The Infectious Pathway: the Scientific Casementioning
confidence: 99%
“…This is followed by inflammation and accelerated degeneration that in turn leads to end plate damage and MC changes as seen on MRI scans [10,23,24];…”
Section: The Infectious Pathway: the Scientific Casementioning
confidence: 99%